2022
DOI: 10.31635/ccschem.021.202100941
|View full text |Cite
|
Sign up to set email alerts
|

Anion-Coordination-Driven Assembly of Anionic Hexagonal and Square Architectures and the Structural Interconversion

Abstract: A biphenyl-bridged bis-tris(urea) ligand L was rationally designed with a favorable angle to construct a hexagon-shaped A 6 L 6 (A = anion) complex upon assembly with phosphate anions (PO 4 3− ) via anioncoordination-driven assembly (ACDA). Due to the moderate flexibility of L, another well-defined discrete architecture, a square-like A 4 L 4 complex, has also been obtained from ligand L and PO 4 3− . Interconversion between these two self-assemblies can be readily realized by solvent regulation. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…In the pursuit of more well‐defined ‘aniono’‐supramolecular polygons by using tris(urea) building block, Yang, Wu and co‐workers checked angles between the linkers and PO 4 3− in the reported tris(urea) complexes and therefore designed a C 2 ‐symmetric biphenyl‐bridged bis‐tris(urea) ligand 32 (Figure 18) for construction a hexagon‐shaped phosphate complex by coordination with PO 4 3− anions in acetonitrile (Figure 20). [66] Crystal structure of the A 6 L 6 hexagon‐shaped architecture 32 6 (PO 4 ) 6 showed that six PO 4 3− anions located at the corners and six ligands lying on the edges of hexagon. A total of 72 hydrogen bonds were observed in one discrete hexagon.…”
Section: Anion‐coordination‐driven Polygonsmentioning
confidence: 99%
“…In the pursuit of more well‐defined ‘aniono’‐supramolecular polygons by using tris(urea) building block, Yang, Wu and co‐workers checked angles between the linkers and PO 4 3− in the reported tris(urea) complexes and therefore designed a C 2 ‐symmetric biphenyl‐bridged bis‐tris(urea) ligand 32 (Figure 18) for construction a hexagon‐shaped phosphate complex by coordination with PO 4 3− anions in acetonitrile (Figure 20). [66] Crystal structure of the A 6 L 6 hexagon‐shaped architecture 32 6 (PO 4 ) 6 showed that six PO 4 3− anions located at the corners and six ligands lying on the edges of hexagon. A total of 72 hydrogen bonds were observed in one discrete hexagon.…”
Section: Anion‐coordination‐driven Polygonsmentioning
confidence: 99%
“…7,8 In order to enhance the understanding of this biotransformation process with specific functions, chemists have made a lot of effort to construct artificial supramolecular systems to mimic these biochemical processes. 9–24 In consideration of their dynamic and reversible features, metal–ligand coordination bonds have been widely used to construct these artificial systems with the ability of structural transformation via dissociation and recombination between the building blocks. 21–38…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In order to enhance the understanding of this biotransformation process with specific functions, chemists have made a lot of effort to construct artificial supramolecular systems to mimic these biochemical processes. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] In consideration of their dynamic and reversible features, metalligand coordination bonds have been widely used to construct these artificial systems with the ability of structural transformation via dissociation and recombination between the building blocks. [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] The unique 4f electronic configurations endow lanthanide ions with rich optical, electrical, magnetic, and catalytic properties, and they are widely used in modern industries such as imaging, laser, superconductivity, batteries and catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the well-studied metal-coordinated assemblies, construction of discrete and well-defined architectures by the anion-coordination-driven assembly (ACDA) strategy represents a rapidly emerging theme in supramolecular chemistry. 24–29…”
mentioning
confidence: 99%
“…In addition to the well-studied metal-coordinated assemblies, construction of discrete and well-defined architectures by the anion-coordination-driven assembly (ACDA) strategy represents a rapidly emerging theme in supramolecular chemistry. [24][25][26][27][28][29] Our group has been active in exploring functional anioncoordination-driven supramolecular assemblies and obtained a series of well-defined architectures, such as tetrahedral cages, by using the bis(urea) building block and phosphate anion, which have been proven to form an excellent coordination interaction involving twelve complementary hydrogen bonds. 30,31 The tetrahedral anion cage 1 NO2 , assembled from 1,3,5-triphenylbenzene-based tris(bisurea) ligand L NO2 , could readily trap a range of (quasi)-tetrahedral halocarbons, 32 such as the Freon components and chlorocarbons, providing the possibility for HHC detection.…”
mentioning
confidence: 99%